Development of an affordable light emitting diode spectrophotometer paired with a Python program for calibration and linearity testing and the measurement of uranium(VI) - Vibho, Amrutaa; Rogat, Courtney; Karavas, Emily; Mohammed, Rahisa; Ogadi, Peace; White, Michael; Salois, Thomas; Anderson, Charles; Prairie, Michael W.; Frisbie, Seth H.; Gallant, Sarah K. (PloS one, 2024)
Uranium (U) is a radiologically and chemically toxic element that occurs naturally in water, soil, and rock at generally low levels. However, anthropogenic uranium can also leach into groundwater sources due to mining, ore refining, and improper nuclear waste management. Over the last few decades, various methods for measuring uranium have emerged; however, most of these techniques require skilled scientists to run samples on expensive instrumentation for detection or require the pretreatment of samples in complex procedures. In this work, a Schiff base ligand (P1) is used to develop a simple spectrophotometric method for measuring the concentration of uranium (VI) with an accurate and affordable light-emitting diode (LED) spectrophotometer. A test for a higher-order polynomial relationship was used to objectively determine the calibration data’s linearity. This test was done with a Python program on a Raspberry Pi computer that captured the spectrophotometer’s calibration and sample measurement data.